2005
DOI: 10.1080/14631370500204370
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Credit Market Imperfections on Farm Investment in Poland

Abstract: The objective of this article is to confirm the presence of imperfections on the rural credit market in Poland in the second half of the transition period, and to identify farms that were the most affected by these imperfections. For this, an investment accelerator model augmented with a cash flow variable was used on panel data for individual farms during 1996-2000. The cash flow coefficient was found to be significant and positive, indicating a poorly functioning rural credit market, in the sense that for so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 15 publications
1
31
1
3
Order By: Relevance
“…Literature on access to inance in the agriculture and organic production in transitional countries is mainly focused on the supply side of the problem, usually including banks and microinance institutions. Development organizations (USAID, EBRD, OECD) are mainly dealing with the constraints and statistics, while researchers are focused on the relationship between credit supply and farm productivity, farm inputs and outputs, investments and other aspects of rural development (for details see Swinnen, Gow, 1999;Swinnen, 2007;Latruffe, 2005;Latruffe et al, 2010). It is reasonable to expect that almost all studies have found positive relationship between an increased access to inance and improvement of analyzed parameters.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Literature on access to inance in the agriculture and organic production in transitional countries is mainly focused on the supply side of the problem, usually including banks and microinance institutions. Development organizations (USAID, EBRD, OECD) are mainly dealing with the constraints and statistics, while researchers are focused on the relationship between credit supply and farm productivity, farm inputs and outputs, investments and other aspects of rural development (for details see Swinnen, Gow, 1999;Swinnen, 2007;Latruffe, 2005;Latruffe et al, 2010). It is reasonable to expect that almost all studies have found positive relationship between an increased access to inance and improvement of analyzed parameters.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Previous research provides evidence of capital market imperfections in Central and Eastern European (CEE) countries during transition and after accession to the European Union (EU) (Latruffe, 2005;Bojnec & Latruffe, 2011). Some papers tested the persistence of soft budget constraints in transition economies.…”
Section: Introductionmentioning
confidence: 99%
“…There is a wealth of research on farm investment (e.g., Bierlen & Featherstone, 1998;Benjamin & Phimister, 2002;Petrick, 2004a,b;Latruffe, 2005;Bakucs et al, 2009;Bokusheva et al, 2009;Zynch & Odening, 2009;Latruffe et al, 2010;Hüttel et al, 2010;Bojnec & Latruffe, 2011;Kallas et al, 2012). However, studies dealing with agriculture are generally limited to one country and exclude cross-country comparisons, except for Benjamin & Phimister (2002), who compared France and the United Kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…Credit constraints were a major problem for growth and restructuring during transition (Swinnen and Gow, 1999) and were still considered an important problem at the time of accession in several of the NEMS (Bezemer, 2003;Latruffe, 2005;Petrick, 2004;Petrick and Latruffe, 2003;World Bank, 2001). …”
Section: Introductionmentioning
confidence: 99%